Rice response to sublethal rates of paraquat, metribuzin, fomesafen, and cloransulam-methyl at different application timings. (6th October 2021) - Lawrence, Benjamin H.; Bond, Jason A.; Golden, Bobby R.; Allen, Tom W.; Reynolds, Daniel B.; Bararpour, Taghi M.
Abstract: The application of paraquat mixtures with residual herbicides before planting rice is a common treatment in Mississippi, and rice in proximity is susceptible to off-target movement of these applications. Four concurrent studies were conducted in Stoneville, MS, to characterize rice performance following exposure to a sublethal rate of paraquat, metribuzin, fomesafen, and cloransulam-methyl at different application timings. Herbicides were applied to rice at the growth stages of spiking to one-leaf (VEPOST), two- to three-leaf (EPOST), three- to four-leaf (MPOST), 7 d postflood (PFLD), and panicle differentiation (PD). Regardless of application timing, rice injury following exposure to paraquat was ≥45%. Delays in maturity were increased by 0.3 d d −1 following paraquat from emergence through PD. Dry weight, rough rice yield, panicle density, and germination were reduced by 18.7 g, 131.5 kg ha −1, 5.6 m −2, and 0.3%, respectively, per day from application of paraquat at emergence through PD. By 28 d after treatment (DAT), metribuzin injured rice 3% to 6%, and that injury did not translate into a yield reduction. Regardless of application timing, rice injury following fomesafen application ranged from 2% to 5% 28 DAT. Rice exposed to cloransulam-methyl EPOST exhibited the greatest root and foliar injury 21 DAT and 28 DAT, respectively. Additionally, when rice was exposed to cloransulam-methyl EPOST, yield was reduced to 6, 540 kg ha −1 compared with a yield of 7, 850 kg ha −1 from nontreated rice. Rice yield was negatively affected after paraquat was applied any time after rice emergence. However, applications of paraquat to rice at early reproductive growth stages reduced rough rice yield and seed germination the greatest. Application timing is crucial in determining severity of rice injury. Early-season injury to rice following paraquat application had less effect on yield compared with injury at later stages. Additionally, fields devoted to seed rice production are at risk for reduced seed germination if they are exposed to paraquat during early reproductive growth stages.